Valorization of Low-Nitrogen, High-Organic-Load Shrimp Aquaculture Wastewater by Dunaliella salina: Pollutant Removal and High-Value-Biomass Production - Alvaro Barreto; Victor Manuel Luna-Pabello; Manuel Sacristán de Alva; Iveth Gabriela Palomino Albarrán; Martín Arenas; Gabriela Gaxiola (Microorganisms, 2025)
The rapid expansion of shrimp aquaculture has led to the generation of nutrient-rich effluents, which contribute to environmental degradation if inadequately managed. This study evaluated the potential of Dunaliella salina for the reuse of shrimp aquaculture wastewater (SAW) in biofloc production systems under varying dilution levels (0%, 25%, and 50%) and the simultaneous production of high-value biomass. Growth kinetics were modeled using a four-parameter logistic model, and nutrient removal, biochemical composition, and fatty acid profile were assessed. D. salina exhibited substantial growth in undiluted SAW, achieving over 80% removal of total nitrogen and reducing the organic load, as measured by a chemical oxygen demand reduction of more than 79%. In SAW treatments, the protein content ranged from 24.7% to 26.3%, while the lipid content reached up to 67.1% in a 25% SAW dilution. Chlorophyll a and total carotenoids were measured at 5.3–7 µg/mL and 4.1–5.7 µg/mL, respectively, in SAW treatments. The polyunsaturated fatty acid content in undiluted SAW was 34.5%, with α-linolenic acid (C18:3n3) and linoleic acid (C18:2n6) comprising 12% and 7.5%, respectively. This study demonstrates the ability of D. salina to valorize shrimp aquaculture wastewater in biofloc systems into lipid-rich, bioactive biomass, supporting its use in integrated aquaculture biotechnology systems for sustainable wastewater management and bioproduct generation.